Typology of visitors to religious tourism destinations from scientific production (2021)
This article addresses the characterization of the typology of visitors to religious tourism destinations. Therefore, the research question is aimed at understanding what the typology of visitors to religious tourism destinations is and how this allows its conceptualization based on scientific production. The focus of this study is the qualitative and documentary types of research. The review and analysis of 52 documents were included along with data from Brazil, Spain, and Mexico which have been the countries that have published the most on religious tourism. This issue is primarily addressed by researchers such as touristologists, economists, geographers, and anthropologists. The main findings focus on the fact that visitors to religious tourism destinations are primarily classified as pilgrims, religious tourists, and cultural tourists.